Pembelajaran Agama Islam Pada Anak Berkebutuhan Khusus di Sekolah - Moch. Bachrurrosyady Amrulloh Rosyady; Umi Faridhotul Afifah (Academia Publication, 2022)
Islamic Education Learning for speech-impaired children is not easy as we think, but it is a regular, continuous and systematic effort, therefore a learning building is needed which is expected to be able to fill the plot so that in this study an overview of the learning process of Islamic Education for speech-impaired children is found at State Elementary School in Sugihwaras Bojonegoro as well as various supporting and inhibiting factors. The results of this study are expected to be used as a concrete model of PAI learning for speech-impaired children. The results of the study show that the learning process for Islamic Religious Education for the speech-impaired at State Elementary School in Sugihwaras Bojonegoro is different from the learning for normal children in general. Learning is done through three stages, namely: planning, implementation, and evaluation. Supporting factors the learning of Islamic Religious Education for the speech impaired are the existence of extracurricular activities, the existence of a library which is of course very useful for increasing the knowledge of mute children, and cooperation between fellow teachers at State Elementary School in Sugihwaras Bojonegoro. While the inhibiting factors are the differences in the characteristics of students, the different intelligence of children, the lack of attention from parents, and the limited facilities and infrastructure. Key Words: Islamic Educational Learning, Speech-impaired Children